2007
DOI: 10.1038/sj.gt.3302947
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral vectors for cancer immunotherapy: transforming infectious particles into therapeutics

Abstract: Lentiviral vectors have emerged as promising tools for both gene therapy and immunotherapy purposes. They exhibit several advantages over other viral systems in that they are less immunogenic and are capable of transducing a wide range of different cell types, including dendritic cells (DC). DC transduced ex vivo with a whole range of different (tumor) antigens were capable of inducing strong antigen-specific T-cell responses, both in vitro and in vivo. Recently, the administration of lentiviral vectors in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
94
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 182 publications
(167 reference statements)
0
94
2
Order By: Relevance
“…19 Several studies have shown that HIV-1-based lentivectors are able to deliver genes into non-dividing and less proliferating cells, including peripheral DCs. [20][21][22][23] One advantage of using the lentivector system is that the vector does not encode any major viral proteins. This eliminates the generation of competition of anti-vector responses, which competes with the generation of anti-transgene responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Several studies have shown that HIV-1-based lentivectors are able to deliver genes into non-dividing and less proliferating cells, including peripheral DCs. [20][21][22][23] One advantage of using the lentivector system is that the vector does not encode any major viral proteins. This eliminates the generation of competition of anti-vector responses, which competes with the generation of anti-transgene responses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lentivectors have thus been proposed to be an ideal vector tool for vaccine delivery. 20,[24][25][26][27][28][29][30][31][32][33] Based on the study of Sindbis virus, a member of the Alphavirus genus and the Togaviride family, we have reported a mutant Sindbis virus glycoprotein, (SVGmu) which can specifically bind to DC-specific intracellular adhesion molecule (ICAM) 3 grabbing non-integrin (DC-SIGN, CD209). 34 DC-SIGN is a C-type lectin-like receptor and is expressed on DCs and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Direct injection of lentivectors into mice does transduce DCs, leading to antigen-specific CD8 + T cell responses and anti-tumor immunity. [19][20][21][22] However, these recombinant viral vectors usually have broad specificity and transduce multiple cell types. Development of viral vectors capable of transducing DCs in a cell-specific manner in vivo could potentially improve the safety and efficacy of vaccination.…”
mentioning
confidence: 99%
“…Although scale up of the co-transfection approach remains a challenge, this method is versatile in allowing production of lentivectors which can be pseudotyped with a variety of viral proteins with different cell type tropisms (see reviews by 40,41 . Recombinant lentivector pseudotyped with envelope protein from different viruses results in preferential transductions of restricted cell types, enabling partial targeting.…”
Section: Lentivector Developmentmentioning
confidence: 99%